TalkZones: Section-based Time Support for Presentations - Saket, Bahador; Yang, Sijie; Tan, Hong Z; Yatani, Koji; Edge, Darren (MobileHCI 2014 Conference on Human Computer Interaction with Mobile Devices and Services, 2014)
Managing time while presenting is challenging, but mobile devices offer both convenience and flexibility in their ability to support the end-to-end process of setting, refining, and following presentation time targets. From an initial HCI-Q study of 20 presenters, we identified the need to set such targets per “zone” of consecutive slides (rather than per slide or for the whole talk), as well as the need for feedback that accommodates two distinct attitudes towards presentation timing. These findings led to the design of TalkZones, a mobile application for timing support. When giving a 20-slide, 6m40s rehearsed but interrupted talk, 12 participants who used TalkZones registered a mean overrun of only 8s, compared with 1m49s for 12 participants who used a regular timer. We observed a similar 2% overrun in our final study of 8 speakers giving rehearsed 30-minute talks in 20 minutes. Overall, we show that TalkZones can encourage presenters to advance slides before it is too late to recover, even under the adverse timing conditions of short and shortened talks.
Honorable Mention Award